2007
DOI: 10.1007/s10038-007-0162-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of the HTRA1 gene variant with age-related macular degeneration in the Japanese population

Abstract: The purpose of this investigation was to determine whether the high-temperature requirement A-1 (HTRA1) gene polymorphism is associated with age-related macular degeneration (AMD) in native, unrelated Japanese patients. A total of 123 patients with AMD and 133 control subjects without AMD were recruited for this study. The single-nucleotide polymorphism (SNP) rs11200638 in the HTRA1 gene was assessed using a TaqMan assay. The risk A allele frequencies in the AMD cases and control patients were 0.577 and 0.380,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 45 publications
0
23
1
Order By: Relevance
“…Recently, HTRA1 also has been reported to occur with the same frequency among Japanese patients with AMD,20 and there was no significant difference between PCV and typical exudative AMD 21. Thus, PCV and typical AMD are similar in some pathophysiological aspects.…”
mentioning
confidence: 84%
“…Recently, HTRA1 also has been reported to occur with the same frequency among Japanese patients with AMD,20 and there was no significant difference between PCV and typical exudative AMD 21. Thus, PCV and typical AMD are similar in some pathophysiological aspects.…”
mentioning
confidence: 84%
“…However, other studies targeting 10q26 for typical nAMD or PCV in Asian populations showed that differences between the sexes are present. 4,20,22,23,25,27,35,36 In addition, all of these studies reported that the association of 10q26 is real even after correction for sex. However, future studies of Asian populations in which sex differences are eliminated are needed to determine the genetic contribution of 10q26 to typical nAMD and PCV.…”
Section: Discussionmentioning
confidence: 94%
“…We also added rs11200638, which has been shown to have a strong association with typical nAMD and PCV, to the selected 18 SNPs for genotyping. 20,[22][23][24][25]27,28 All of the SNPs 10q26 HAPLOTYPES IN JAPANESE WITH NEOVASCULAR AMD were genotyped using the Taqman SNP genotyping assay (Applied Biosystems, Foster City, CA, USA).…”
Section: Snp Selection and Genotypingmentioning
confidence: 99%
“…In addition, one of the major and important neovascular AMD genes, the HtrA serine peptidase 1 (HTRA1) gene at location 10q26, has been identified in both Caucasian and Chinese patients [3,21]. HTRA1 also has been reported equally in Japanese patients with AMD [16,22]. Some researchers have reported that the LOC387715/HTRA1 variants or ARMS2 (age-related maculopathy susceptibility 2)/HTRA1 variants were associated with PCV and typical AMD in a Japanese population, which suggested that PCV and typical AMD are similar in genetic susceptibility [4,5,11].…”
Section: Discussionmentioning
confidence: 97%